CROSS SECTIONAL DATA ANALYSIS OF YOUNG PEOPLE'S HOPE LEVELS IN TURKEY - Demir Toker, Çiğdem; Toker, Boran; Polat, Buğra (International Journal of Contemporary Economics and Administrative Sciences, 2021)
In the study, the factors affecting the levels of hope for young individuals were examined through cross-sectional data analysis. For this purpose, the data of the TURKSTAT Life Satisfaction Survey data set for the years 2013-2017 were handled and the hope levels of the youth were accepted as the dependent variable. Young individuals between the ages of 15-29 were selected from the data set, considering the length of presence in education and since it is thought that the individual determines the hope level of young people, the education level, the predictions about their own situation in the next 5 years and the predictions about the economic and social situation of the country in the next 5 years are added to the model as independent variables. Initially, estimates were made using the ordinal logit model, but since the education independent variable did not satisfy the parallel slopes assumption of the primary education category, generalized ordinal logit and partial proportional odds models were used. According to the results obtained from the model, it was seen that the increase in the education level of the young people increased their hope level, and their positive thoughts about the future both about their own situation as well as economic and social situation of the country.